Deformation behavior of semi-solid hypereutectic Al-Si alloy compressed in the drop-forge viscometer - Daisaku NARA; Noriyoshi KUMAZAWA; Yasuyoshi FUKUI (Nihon Kikai Gakkai ronbunshu, 2014)
The aim of this study is to investigate the rheological behavior for a semi-solid forming of Al−25 mass % Si alloy, i.e., hypereutectic Al-Si alloy, using a self-made parallel-plate drop-forge viscometer. Drop-forge experiments show individually the features that the viscosity decreased in the early increasing shear rate stage and subsequently the viscosity turned to increase as the shear rate decreased. Thus, the viscosity takes a minimum around the maximum shear rate. The summarized behavior between the viscosity, μ[Pa･s], and the shear rate, γ [s-1], can be described by a power-law model of μ＝1.78×107γ-1.5. The decrease in viscosity accompanied with the increase in the shear rate depends on both rises in the temperature and the applied force, not the duration of forging. The convex shape curve is observed between the effective duration and the viscosity and the effective duration reaches a maximum at around μ＝30 kPa･s where γ=70 s-1. The origin of the profile is due to the lost of ability to transform the kinetic energy to distortion energy, which is caused by a decrease of deformation resistance accompanied with a decrease of viscosity. Then the viscosity μ＝30 kPa･s, which corresponds to the transition point from plastic forming to casting, seems to be the optimum condition for semi-solid forming.